Investigating the Effect of Fresh Frozen Plasma and Albumin on DNA Damage and Oxidative Stress Biomarkers in Poisoning Cases by Organophosphates - Afzali, Saeed; Karami, Manoochehr; Kheyripour, Nejat; Ranjbar, Akram (Drug Research, 2020)
The efficacy of albumin and fresh frozen plasma (FFP) and their effects on biomarkers of oxidative stress has been evaluated. In a randomized clinical control trial, 33 poisoned patients by Organophosphate (OP) were enrolled in the research and divided into three groups. The first group underwent conventional treatments by atropine and pralidoxime (control group); the second and third groups, in addition to traditional treatments, received albumin and FFP. Cholinesterase (ChE) enzyme activity, total antioxidant capacity (TAC), serum thiol groups (TTG), malonyl aldehyde (MDA) and DNA damage were measured in all treatment and control groups. Patients were matched in terms of demographic characteristics at the beginning of the study. ChE activity was increased in all three groups during treatment, which was more noticeable in the FFP group and was statistically significant in both albumin and FFP group compared to the control group (p<0.05). TAC increased, and TTG decreased in FFP and albumin groups compared to the control group; no significant difference was observed. MDA decreased in albumin and FFP and was significantly different in the FFP group compared to the control group (p<0.05). The amount of DNA damage in FFP and albumin groups decreased, and there was a significant difference compared to the control group (p<0.05). According to the results of this study, due to the decrease of oxidative damage parameters and the increase of antioxidant parameters in albumin and specially FFP groups, FFP may be considered as an adjunctive treatment for OP poisoning.
Keywords: organophosphate; poisoning; cholinesterase activity; antioxidants; albumin; fresh frozen plasma